THE DESIGN AND EFFICACY OF INTERACTIVE DIGITAL SIMULATIONS FOR PRESCHOOL COGNITIVE DEVELOPMENT: INTEGRATING PIAGET’S PREOPERATIONAL THEORY AND MAYER’S MULTIMEDIA PRINCIPLES - Junaedi, Lukman; Arif, Muchamad; Virdaus, Varia Virdania; Rofiyarti, Fitri; Faviandhani, Qausya (Universitas Narotama, 2025)
Early Childhood Education (ECE) plays a critical role in shaping foundational cognitive skills, particularly during the preoperational stage (ages 2–7 years) as theorized by Jean Piaget. Children in this phase learn optimally through active, symbolic manipulation and play. However, the global shift towards digital learning necessitates a robust instructional design framework to overcome the limitations of passive media and mitigate the risks of cognitive overload often associated with poorly structured digital content. This study addresses the urgent need for empirically validated, theory-driven digital learning tools for ECE by systematically integrating Piaget’s developmental rationale with Richard E. Mayer’s Cognitive Theory of Multimedia Learning (CTML). The research employed a systematic Research and Development (R&D) approach using the five-phase ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The analysis phase defined specific cognitive targets (e.g., shape, number, and color recognition) suitable for preoperational learners. The design and development phases strictly implemented key CTML principles, such as the Coherence Principle (eliminating extraneous materials like non-essential background music) and the Modality Principle (using audio narration instead of on-screen text to prevent dual-channel overload), thereby optimizing cognitive processing efficiency for young learners. The intervention—an interactive digital simulation designed around these principles—was implemented with a sample of ECE children in Indonesia. The efficacy of the intervention was evaluated using a pre-test post-test quasi-experimental design. The results demonstrated a statistically significant improvement in the cognitive performance of the treatment group (p < 0.05). Specifically, children exposed to the CTML-designed simulation showed an average cognitive gain of 25% to 30% in targeted skills (classification, counting, and problem-solving) compared to their baseline scores. This substantial gain validates the combined theoretical approach. The study concludes that the effectiveness of digital media in ECE is not inherent to the technology itself but is directly proportional to the rigor of the instructional design, confirming that minimizing extraneous cognitive load through Mayer's principles enables more efficient assimilation and accommodation of new knowledge, aligning perfectly with Piagetian demands for active learning. Future research should explore the long-term retention effects and integrate more immersive technologies like Augmented Reality (AR).10Keywords: Interactive Digital Learning; Cognitive Development; Piaget's Preoperational Stage; Multimedia Learning Principles. Keywords: Interactive Digital Learning; Cognitive Development; Piaget's Preoperational Stage; Multimedia Learning Principles